2016
DOI: 10.1007/s10826-016-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Daughter Relationship Quality and Body Image in Preadolescent Girls

Abstract: Research suggests that mothers may play a role in girls' body image development. The ''interactive'' hypothesis specifies that qualities of the mother-daughter relationship, as opposed to maternal modeling alone, predict daughter's body image. We sought to understand how maternal relationship quality, from the perception of both daughters and mothers, was associated with preadolescent girls' body image. The relationship between motherdaughter relationship quality and daughters' body image was examined in 152 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…Conversations about weight between mothers and daughters may lead daughters to think that it is appropriate to evaluate their own bodies negatively and self-objectify since they have witnessed and participated in such conversations without any negative consequences (Arroyo & Andersen, 2016; Smith et al, 2016). Studies have shown that women often receive implicit rewards (compliments) for negatively discussing their body (Nichter, 2000) which subconsciously encourages them to continue such behavior.…”
Section: Influence Of Mothersmentioning
confidence: 99%
“…Conversations about weight between mothers and daughters may lead daughters to think that it is appropriate to evaluate their own bodies negatively and self-objectify since they have witnessed and participated in such conversations without any negative consequences (Arroyo & Andersen, 2016; Smith et al, 2016). Studies have shown that women often receive implicit rewards (compliments) for negatively discussing their body (Nichter, 2000) which subconsciously encourages them to continue such behavior.…”
Section: Influence Of Mothersmentioning
confidence: 99%
“…were aware of potential harms of HCBs, and at the same time, managed intimate mother-daughter relationship. Previous studies have suggested that mother-daughter relationship may be inversely associated with body image and health behavior [41,42] The prevalence of HCB consumption was 26.7% for boys and 20.9% for girls in 2017. This is higher than 11.9-14.1% reported in earlier studies [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual Well-being among Gender-Diverse Youth For many youth, body image development begins at an early age, with children as young as three identifying that thin bodies are better than fat bodies and communicating a desire to be thin (Smith et al, 2016). Body image is a complex construct that includes the feelings and attitudes individuals hold toward their body and the investment they make in their appearance (Cash & Pruzinsky, 1990).…”
Section: Intersections Between Body Image Sexual Identity Andmentioning
confidence: 99%